Making roads safer: a vehicle blind spot alert system co-designed with end-users - Lisboa, Pedro; Dos Santos, Felipe; Ribeiro, Herick; Campos, Pietro; Zaina, Luciana (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
The number of traffic accidents involving motorcycles has been increasing in Brazil recently. Many accidents are caused by drivers who do not see motorcycles approaching in the vehicle blind spots. Advanced Driver Assistance Systems (ADAS) installed in vehicles can be used to mitigate this problem. However, the development of ADASs often focuses on security issues and does not consider the user experience with the ADASs interface. In this paper, we present the design of an alerting system that warns drivers about collision risks when motorcycles are identified in vehicle blind spots. Our proposal alerts drivers by using visual and haptic interaction modes. The vehicle blind spot alert system was conceived in a co-design session with the participation of 9 end-users who produced 3 low-fidelity (lo-fi) prototypes. After, these lo-fi prototypes were analyzed and compiled generating a high-fidelity (hi-fi) prototype containing haptic and visual alerting features implemented and installed in a car for testing. The alert system was evaluated by 20 end-users concerning their experience with the different warning modes. The results showed that for both the visual and haptic modes, users could recognize and understand the alerts without employing a great effort in the information interpretation. This result reinforces the idea that ADASs should provide simple interpretative interfaces because drivers' interaction with these systems should be a secondary activity since their concentration must be on driving.